Radiation dose reduction in digital plain radiography of the knee after total knee arthroplasty - Kloth, Jost; Tanner, Michael Christopher; Kauczor, Hans-Ulrich; Ewerbeck, Volker; Weber, Marc-André (RöFo, 2015)
Purpose: To reduce radiation exposure of frequently performed radiographs of the knee in follow-up of total-knee arthroplasty ensuring accurate assessment by using objective quality control criteria. Materials and Methods: In this prospective randomized study 278 radiographs of the knee in follow-up of total-knee arthroplasty were performed with standard and 37% reduced radiation dose. The evaluation of the plain-radiographs was conducted using the following criteria: bone-implant interface, implant-surface character, implant-implant discrimination and periarticular heterotopic ossification. Two radiologists evaluated these criteria using a score ranging from 1 (definitely assessable) to 4 (not assessable). If a single criterion had been evaluated with a score ≥3 or more than 2 criteria with ≥2 points, the radiograph was score das „not assessable“. The study was designed as non-inferiority-trial. Results: 100% of examined radiographs were scored as assessable, hence no statistical inferiority between the examinations with standard and reduced dose could be observed. Singular assessment of the defined criteria was likewise dose-independent. Conclusion: Plain-radiography of the knee following total-knee arthroplasty can be performed with 63% of standard dose without loss of diagnostic validity. Key points: • Due to the non-inferiority of digital radiographs of the knee joint after total-knee arthroplasty done with 37% reduced image receiver dose we recommend the tested speed class of SC 800 as a new reference value for digital radiographs with this indication. Citation Format: • Kloth JK, Tanner M, Stiller W etal. Radiation Dose Reduction in Digital Plain Radiography of the Knee after Total Knee Arthroplasty. Fortschr Röntgenstr 2015; 187: 685-690
Gesehen am 16.02.2017